Phylogenetic analysis and predicted functional effect of protein mutations of E6 and E7 HPV16 strains isolated in Indonesia (Faculty of Medicine Universitas Indonesia, 2015)
Background: E6 and E7 are oncoproteins of HPV16. Natural amino acid variation in HPV16 E6 can alter its carcinogenic potential. The aim of this study was to analyze phylogenetically E6 and E7 genes and proteins of HPV16 from Indonesia and predict the effects of single amino acid substitution on protein function. This analysis could be used to reduce time, effort, and research cost as initial screening in selection of protein or isolates to be tested in vitro or in vivo. Methods: In this study, E6 and E7 gene sequences were obtained from 12 samples of Indonesian isolates, which were compared with HPV16R (prototype) and 6 standard isolates in the category of European (E), Asian (As), Asian-American (AA), African-1 (Af-1), African-2 (Af-2), and North American (NA) branch from Genbank. Bioedit v.7.0.0 was used to analyze the composition and substitution of single amino acids. Phylogenetic analysis of E6 and E7 genes and proteins was performed using Clustal X (1.81) and NJPLOT softwares. Effects of single amino acid substitutions on protein function of E6 and E7 were analysed by SNAP. Results: Java variants and isolate ui66* belonged to European branch, while the others belonged to Asian and African branches. Twelve changes of amino acids were found in E6 and one in E7 proteins. SNAP analysis showed two non neutral mutations, i.e. R10I and C63G in E6 proteins. R10I mutations were found in Af-2 genotype (AF472509) and Indonesian isolates (Af2*), while C63G mutation was found only in Af2*. Conclusion: E6 proteins of HPV16 variants were more variable than E7. SNAP analysis showed that only E6 protein of African-2 branch had functional differences compared to HPV16R.